REPRESENTASI MULTIKULTURAL BUDAYA DALAM NOVEL GADIS PESISIR KARYA NUNUK Y. KUSMIANA - Pripta Fajri Ramadhanti; Candra Rahma Wijaya Putra (Kantor Bahasa Provinsi Maluku Utara, 2020)
The purpose of this study is to describe the following: (1) cultural elements that emerge in transmigration communities in the novel Pantai Pesisir by Nunuk Y Kusmiana, (2) the form of cultural mixing in the Pantai Pesisir Nunuk Y Kusmiana novel. This type of research used in this study is qualitative. The approach used is a descriptive approach. The data source of this research is Novel Girl Coastal Work of Nunuk Y Kusmiana with data in the form of sentence excerpts. The research analysis was carried out with analytical and critical readings based on the Koentjaraningrat multiculturalism theory. The data analysis technique used is the note and note technique. The results of the description are then concluded and compiled into a journal article. The results of the research show that the cultural elements that appear in Nunuk Y Kusmiana's Coastal Girl Novel and representations of multicultural communities in the land of Papua.